Exploring The Role of social media In Higher Education: A Case Study - Daniel CHIS; Mihai CARAMIHAI (Communications of International Proceedings, 2022)
As social media has become omnipresent in our lives we need to understand its role in higher education. Through statistical means, we interviewed students on social media correlations with their studies through the Likert Scale and linked the result to our hypothesis. The results showed that social media improves learning performance through collaborative learning, the enrollment and interactions increase between the students and the teachers. The environment created through social media breaks down barriers in communication, bringing the educational space closer to the real word one. Even though it also has a negative impact, the benefits exceed it, creating new educational techniques.
Keywords: digital education; social media education; educational social networks